2019
DOI: 10.2478/fhort-2019-0009
|View full text |Cite
|
Sign up to set email alerts
|

Organic and non-organic mulches – impact on environmental conditions, yield, and quality of Cucurbitaceae

Abstract: The publication presents the current state of knowledge regarding the importance of mulching in the cultivation of Cucurbitaceae (cucurbit, or gourd family) vegetables. The intensifying climate change – mainly decreasing rainfall – combined with large-scale production of cucurbit vegetables worldwide prompt the application of methods that reduce evaporation and weed infestation. One of the widespread methods is mulching of the soil. The most important advantages of this treatment include the efficient use of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 99 publications
0
11
0
Order By: Relevance
“…Many technologies were tested to enhance the availability of water for plants and to protect water loss. It is verified that mulches enhance the availability of water for plants by their impact on reducing erosion, evaporation, surface temperature, wind impact, and weed infestation [37][38][39]. Different researchers reported that coloured plastic mulches have a visible impact on effective water use, protection against water loss, and enhancing water use efficiency for different crops [15,25,39,40].…”
Section: Effect Of Coloured Plastic Mulches On Soil Water and Water Use Efficiencymentioning
confidence: 99%
“…Many technologies were tested to enhance the availability of water for plants and to protect water loss. It is verified that mulches enhance the availability of water for plants by their impact on reducing erosion, evaporation, surface temperature, wind impact, and weed infestation [37][38][39]. Different researchers reported that coloured plastic mulches have a visible impact on effective water use, protection against water loss, and enhancing water use efficiency for different crops [15,25,39,40].…”
Section: Effect Of Coloured Plastic Mulches On Soil Water and Water Use Efficiencymentioning
confidence: 99%
“…Kosterna et al (2010) reported increments in dry matter, reducing sugars (fructose and glucose), and vitamin C in melon as a result of mulching with black polyethylene lm. Other studies have reported that the use of organic mulching had a bene cial effect on the synthesis of dry matter, crude ber, and protein content in pumpkin (Bucki and Siwek 2019). Additionally, the same authors reported increased dry matter content in cucumber fruits of mulched plants, with a similar amount of soluble sugars compared to the fruits from plants grown on non-covered soils.…”
Section: )mentioning
confidence: 80%
“…It is also possible that moisture retained by straw mulch may lead to the production of compounds that may be toxic to the insects in question; this would result in lower populations compared to a cropped area without straw. In many of the studies cited earlier [11][12][13][14][15][16][17], mulching reduced pest numbers generally as a result of enhanced natural enemy activity. If one were to draw a parallel with this study, one would have to conjecture that the beneficial fauna in the case of amaranth and D. glabrata was simply at a very low ebb to exert significant any impact on the adult beetle population.…”
Section: The Role Of Leaf Mulch On D Glabrata Populationmentioning
confidence: 99%